DEVELOPMENT OF SHU CALCULATION AND DEVELOPMENT SYSTEMS (REMAIN BUSINESS RESULTS) ON EMPLOYEE COOPERATIVES “PERDANA ASIA” PT. BANK CENTRAL ASIA, TBK - Onne Sesaphing; Anita Wijayanti; Riana Rachmawati Dewi (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2019)
The purpose of this study is to find out the system of calculation and distribution of SHU (Remaining Business Results) on employee cooperatives